Pulse height tests of a large diameter fast LaBr3:Ce scintillation detector. (October 2015) - Naqvi, A.A.; Khiari, F.Z.; Maslehuddin, M.; Gondal, M.A.; Al-Amoudi, O.S.B; Ukashat, M.S.; Ilyas, A.M.; Liadi, F.A.; Isab, A.A.; Rehman, Khateeb-ur; Raashid, M.; Dastageer, M.A.
Abstract: The pulse height response of a large diameter fast 100 mm×100 mm LaBr3 :Ce detector was measured for 0.1–10 MeV gamma-rays. The detector has a claimed time resolution of 608 ps for 511 keV gamma rays, but has relatively poor energy resolution due to the characteristics of its fast photomultiplier. The detector pulse height response was measured for gamma rays from cobalt, cesium, and bismuth radioisotope sources as well as prompt gamma rays from thermal neutron capture in water samples contaminated with mercury (3.1 wt%), boron (2.5 wt%), cadmium (0.25 wt%), chromium (52 wt%), and nickel (22 wt%) compounds. The energy resolution of the detector was determined from full width at half maximum (FWHM) of element-characteristic gamma ray peaks in the pulse height spectrum associated with the element present in the contaminated water sample. The measured energy resolution of the 100 mm×100 mm detector varies from 12.7±0.2% to 1.9±0.1% for 0.1 to 10 MeV gamma rays, respectively. The graph showing the energy resolution Δ E / E (%) versus 1/√ E γ was fitted with a linear function to study the detector light collection from the slope of the curve. The slope of the present 100 mm×100 mm detector is almost twice as large as the slope of a similar curve of previously published data for a 89 mm×203 mm LaBr3 :Ce detector. This indicates almost two times poorer light collection in the 100 mm×100 mm detector as compared to the other detector. Highlights: Pulse height tests of 100 mm×100 mm cylindrical fast LaBr3 :Ce detector. Prompt gamma ray measurements. Water samples with mercury (3.1 wt%), boron (2.5 wt%), cadmium (0.25 wt%), chromium (52 wt%), and nickel (22 wt%) contamination.